Analisis Pemecahan Masalah Matematika Berbentuk Soal Cerita pada Materi SPLDV Ditinjau dari Gaya Kognitif - Kuswatiningsih, Fitria; Faizah, Hanim (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2022)
Abstract Problem solving skills are very important for learning mathematics. Solving mathematical problems requires strategies that involve cognitive processes in understanding the problem. The purpose of this study is a form of description of students' abilities in solving problem solving on SPLDV material in terms of cognitive style. This type of research is a qualitative descriptive research using a written test and question and answer method. The subjects used in this research were VIII-F students of SMP PGRI 1 Buduran with 2 FD students and 2 FI students. The instruments used include the GEFT test (Group Embedded Figures Test), problem-solving question sheets and interview guidelines. Information analysis includes data reduction, presentation of information and drawing conclusions. The results of the study showed that FD subjects were able to read problems, mastered oral statements from cases and had not been able to replace them with mathematical words, received more detailed information, were unable to expand the results of problem solving and often did not get the right results. On the other hand, FI subjects are able to read problems, master verbal statements from cases and convert them into mathematical words, are more analytical in receiving information, work with their own ideas, can expand the results of problem solving and obtain precise results. The conclusion of this research is that individual FDs are quite capable of fulfilling Newman's problem indicators. On the other hand, FI individuals are able to fulfill Newman's indicators. Keywords: Mathematical problem solving, Field Dependent, Field Independent. Abstrak Keterampilan pemecahan masalah sangatlah penting untuk pembelajaran matematika. Memecahkan masalah matematika membutuhkan strategi yang melibatkan proses kognitif dalam memahami masalah. Tujuan dari penelitian ini merupakan bentuk deskripsi dari kemampuan siswa dalam menyelesaikan pemecahan permasalahan pada materi SPLDV ditinjau dari gaya kognitif. Jenis riset ini merupakan riset deskriptif kualitatif dengan memakai metode uji tulis serta tanya jawab. Subjek yang dipakai pada riset ini merupakan siswa VIII- F SMP PGRI 1 Buduran dengan 2 siswa FD serta 2 siswa FI. Instrument yang dipergunakan mencakup uji GEFT (Group Embedded Figures Test), lembar pertanyaan pemecahan masalah serta pedoman wawancara. Analisa informasi mencakup reduksi data, penyajian informasi serta penarikan kesimpulan. Hasil studi membuktikan subjek FD mampu membaca permasalahan, menguasai statment lisan dari kasus serta belum sanggup mengganti dengan bentuk perkataan matematika, menerima informasi lebih garis besar, tidak sanggup meluaskan hasil penyelesaian permasalahan serta kerap tidak memperoleh hasil yang tepat. Sebaliknya subjek FI mampu membaca permasalahan, menguasai statment lisan dari kasus serta mengubahnya ke wujud perkataan matematika, lebih analitis dalam menerima informasi, bertugas dengan idenya sendiri, bisa meluaskan hasil penyelesaian permasalahan serta memperoleh hasil yang tepat. Simpulan dari riset ini ialah individu FD cukup mampu penuhi indikator permasalahan Newman. Sebaliknya individu FI mampu penuhi indicator Newman. Kata Kunci: Pemecahan masalah matematika, Field Dependent, Field Independent.